Use of Cardiac Computed Tomography and Magnetic Resonance Imaging in Case Management of Atrial Fibrillation with Catheter Ablation - Lee, Hee-Gone (Korean J Radiol, 2019)
Atrial fibrillation (AF) is the most common arrhythmia associated with the risk of morbidity and mortality in clinical patients. AF is considered as an arrhythmia type that develops and progresses through close connection with cardiac structural arrhythmogenic substrates. Since the introduction of catheter ablation-mediated electrical isolation of arrhythmogenic substrates, cardiac imaging indicates improved treatment outcome and prognosis with appropriate candidate selection, ablation catheter guidance, and post-ablation follow-up. Currently, cardiac computed tomography (CCT) and cardiovascular magnetic resonance (CMR) imaging are essential in the case management of AF at both pre-and post-procedural stages of catheter ablation. In this review, we discuss the roles and technical considerations of CCT and CMR imaging in the management of patients with AF undergoing catheter ablation.